BRAF V600E Inhibitor (Vemurafenib) for BRAF V600E Mutated Low Grade Gliomas - Del Bufalo, Francesca; Ceglie, Giulia; Cacchione, Antonella; Alessi, Iside; Colafati, Giovanna Stefania; Carai, Andrea; Diomedi-Camassei, Francesca; De Billy, Emmanuel; Agolini, Emanuele; Mastronuzzi, Angela; Locatelli, Franco (Frontiers in Oncology, 2018)
Low-grade gliomas (LGG) are the most common central nervous system tumors in children. Prognosis depends on complete surgical resection. For patients not amenable of gross total resection new approaches are needed. The BRAF mutation V600E is critical for the pathogenesis of pediatric gliomas and specific inhibitors of the mutated protein, such as Vemurafenib, are available. We investigated the safety and efficacy of Vemurafenib as single agent in pediatric patients with V600E+ LGG. From November 2013 to May 2018, 7 patients have been treated in our Institution; treatment was well-tolerated, the main concern being dermatological toxicity. The best responses to treatment were: 1 complete response, 3 partial responses, 1 stable disease, only one patient progressed; in one patient, the follow-up is too short to establish the clinical response. Two patients discontinued treatment, and, in both cases, immediate progression of the disease was observed. In one case the treatment was discontinued due to toxicity, in the other one the previously assessed BRAF V600E mutation was not confirmed by further investigation. Two patients, after obtaining a response, progressed during treatment, suggesting the occurrence of resistance mechanisms. Clinical response, with improvement of the neurologic function, was observed in all patients a few weeks after the therapy was started. Despite the limitations inherent to a small and heterogeneous cohort, this experience, suggests that Vemurafenib represents a treatment option in pediatric patients affected by LGG and carrying BRAF mutation V600E.